2019
DOI: 10.1097/ftd.0000000000000644
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular Filtration Rate Is a Major Predictor of Clearance of Oxcarbazepine Active Metabolite in Adult Chinese Epileptic Patients: A Population Pharmacokinetic Analysis

Abstract: Background: Oxcarbazepine (OXC) is almost completely metabolized to its10-monohydroxy derivative (MHD), which is responsible for the pharmacological effects of the drug. Several studies have described the population pharmacokinetics (PPK) of MHD in pediatric patients, but little is known about its pharmacokinetics in adult patients. In addition, no study to date has proposed a model to investigate the influence of genetic polymorphisms on MHD pharmacokinetics. The aim of this study was to establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…It was found that eGFR significantly affected MHD CL, according to the observations from Lin et al [29]. In patients with impaired renal function (eGFR: 20–80 mL/min), the CL was 34.8% (9.4%–64.2%) lower than those with normal renal function.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…It was found that eGFR significantly affected MHD CL, according to the observations from Lin et al [29]. In patients with impaired renal function (eGFR: 20–80 mL/min), the CL was 34.8% (9.4%–64.2%) lower than those with normal renal function.…”
Section: Resultsmentioning
confidence: 93%
“…Most PPK analysis was performed in patients with epilepsy [24,26-33], and only Antunes et al [34] enrolled healthy subjects. One study was conducted only in infants [25], seven studies were conducted in children [24,25,27,28,30-32], two studies included both children and adults [26,33], and two studies only enrolled adults [29,34]. Subjects in all the included studies were administered OXC orally, with doses ranging from 75 to 1800 mg/d.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations